Correlation Between Total Cholesterol Level with Blood Pressure of Hypertensive Patients in Kalidoni, Palembang - Tungki Pratama Umar; Mariana Mariana (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2021)
Background: Hypertension is the main problem worldwide. It has strong relationship with other component of metabolic syndrome, namely dyslipidemi. Authors are analyzing the correlation between total cholesterol level and blood pressure in the hypertensive patient at Kalidoni Primary Health Center, Palembang, Indonesia.Methods: This was a cross-sectional study involving 82 adult hypertensive patients. Data were collected from the medical record of patients who are visiting Kalidoni Primary Health Center in December 2019-January 2020. Demographic data, blood pressure, and total cholesterol level were gained. Obtained data are analyzed descriptively (frequency distribution) and analytically (correlation using Pearson or Spearman method).Result: Significant positive correlations were observed between total cholesterol level and systolic blood pressure (r=0.509, p=0.000) in addition to body weight and diastolic blood pressure (r=0.279; p=0.011).Conclusion: Blood cholesterol level had a significant correlation with moderate strength for determining systolic blood pressure level in hypertensive patients.